ANALISIS EFFICIENT MARKET HYPOTHESIS PADA BURSA EFEK INDONESIA TERHADAP PASAR SAHAM ASEAN - Astriyani Prima Kartika; Jubaedah Jubaedah; Fitri Yetti (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
This research aims to analyze the performance of Indonesia Stock Exchange to ASEAN stock market during period 2012-2016. The technique of determining the sample using purposive sampling method and 6 countries as sample are Indonesia, Singapore, Malaysia, Vietnam and Philippines. Hypothesis testing in this study using Descriptive Statistics Analysis, Test Run and Kolomogorov Smirnov with a significance level of 0.05. Test results show that: (1) Indonesia Stock Exchange has the highest efficient rating in ASEAN stock market (2) ASEAN Stock Exchange effect on Indonesia Stock Exchange. (3) The Indonesia Stock Exchange has a stock return pattern that fluctuates normally in the ASEAN stock market.div>